Methoxy and bromo scans on N-(5-methoxyphenyl) methoxybenzenesulphonamides reveal potent cytotoxic compounds, especially against the human breast adenocarcinoma MCF7 cell line - Myriam González; María Ovejero-Sánchez; Alba Vicente-Blázquez; Manuel Medarde; Rogelio González-Sarmiento; Rafael Peláez (Taylor & Francis Group, 2021)
Thirty seven N-(5-methoxyphenyl)-4-methoxybenzenesulphonamide with methoxy or/and bromo substitutions (series 1-4) and with different substituents on the sulphonamide nitrogen have been synthesised. 21 showed sub-micromolar cytotoxicity against HeLa and HT-29 human tumour cell lines, and were particularly effective against MCF7. The most potent series has 2,5-dimethoxyanilines, especially the 4-brominated compounds 23-25. The active compounds inhibit microtubular protein polymerisation at micromolar concentrations, thus pointing at tubulin as the target. Co-treatment with the MDR inhibitor verapamil suggests that they are not MDR substrates. Compound 25 showed nanomolar antiproliferative potency. It severely disrupts the microtubule network in cells and arrests cells at the G2/M cell-cycle phase, thus confirming tubulin targeting. 25 triggered apoptotic cell death, and induced autophagy. Docking studies suggest binding in a distinct way to the colchicine site. These compounds are promising new antitumor agents acting on tubulin.